Religious Moderation Education in The Perspective of Millennials Generation in Indonesia - Susanto susanto; Ayu Desrani; Suci Ramadhanti Febriani; Rosita Ilhami; Saifullah Idris (STAI Hubbulwathan Duri, 2022)
Having religious diversity is a big challenge for people in Indonesia. Welcoming a moderate attitude in religion is currently an important role for every educational unit to create a religiously tolerant society. For this reason, this research was conducted with the aim of measuring and seeing how religious moderation among millennials and millennials' perceptions of the important role of education in creating religious moderates are. To measure and obtain data, researchers conducted a survey of millennial respondents with various professions as many as 80 respondents representing the millennial generation. Data was collected by distributing a questionnaire using the google form platform as many as 14 questions were asked according to the indicators. Then the data is analyzed using triangulation of data sources, namely data collection, data reduction, data presentation, and then draw conclusions. The findings in this study indicate that religious moderation from the perspective of the millennial generation in Indonesia is quite good. This is indicated by several indicators of religious moderation, the millennial generation has shown a commitment to nationalism, tolerance, anti-violence and can accept the local culture.